2019
DOI: 10.1002/mana.201700446
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional m‐quasi Einstein manifolds with degenerate Ricci tensor

Abstract: In this article we give a classification of three dimensional m‐quasi Einstein manifolds with two distinct Ricci‐eigen values. Our study provides explicit description of local and complete metrics and potential functions. We also describe the associated warped product Einstein manifolds in detail. For the proof we present a Codazzi tensor on any three dimensional m‐quasi Einstein manifold and use geometric properties of the tensor which help to analyze the m‐quasi Einstein equation effectively. A technical adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Einstein manifolds with parallel Ricci tensor, and also in [13], they classified m-quasi Einstein manifolds with all eigenvalues of the Ricci tensor as constant. Kim and Shin [14] also classified 3-dimensional m-quasi Einstein manifolds. Barros and Gomes [2] studied compact m-quasi Einstein manifolds and also showed that if such a manifold is Einstein, then its potential vector field vanishes.…”
Section: Introductionmentioning
confidence: 99%
“…Einstein manifolds with parallel Ricci tensor, and also in [13], they classified m-quasi Einstein manifolds with all eigenvalues of the Ricci tensor as constant. Kim and Shin [14] also classified 3-dimensional m-quasi Einstein manifolds. Barros and Gomes [2] studied compact m-quasi Einstein manifolds and also showed that if such a manifold is Einstein, then its potential vector field vanishes.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we study three-dimensional Riemannian manifolds with two distinct Ricci eigenvalues having a nonzero solution to (2). This paper is the result of efforts devoted toward refining and generalizing [26], which concerns three-dimensional m-quasi Einstein manifolds. We preferentially study the common properties of spaces for general ψ(f ) and φ(f ).…”
Section: Introductionmentioning
confidence: 99%
“…
In this paper, we study a three-dimensional Ricci-degenerate Riemannian manifold (M 3 , g) that admits a smooth nonzero solution f to the equationwhere ψ, φ are given smooth functions of f , Rc is the Ricci tensor of g. Spaces of this type include various interesting classes, namely gradient Ricci solitons, m-quasi Einstein metrics, (vacuum) static spaces, V -static spaces, and critical point metrics.The m-quasi Einstein metrics and vacuum static spaces were previously studied in [26,24], respectively. In this paper, we refine them and develop a general approach for the solutions of (1); we specify the shape of the metric g satisfying (1) when ∇f is not a Ricci-eigen vector.
…”
mentioning
confidence: 99%
See 1 more Smart Citation